Gray wolves in an anthropogenic context on a small island in prehistoric Scandinavia - Girdland-Flink, Linus; Bergström, Anders; Storå, Jan; Ersmark, Erik; Apel, Jan; Krzewińska, Maja; Dalén, Love; Götherström, Anders; Skoglund, Pontus (Proceedings of the National Academy of Sciences - PNAS, 2025)
Dogs were domesticated at least once from a yet-unidentified wolf population at least ~15,000 y ago. However, how domestication took place is a topic of ongoing debate, and the ability of human groups to manage wolves in their communities during early stages of domestication is poorly understood. Here, we report multiproxy data from two canids excavated from Late Neolithic and Bronze Age contexts in the Stora Förvar cave on the island of Stora Karlsö in the Baltic Sea. The island is small (2.5 sq km) and, like the neighboring island of Gotland, carries no endemic populations of terrestrial mammals. Instead, the current consensus is that human introductions account for some mammal fauna on Gotland, and for the majority of that on Stora Karlsö. Genome-wide data show that the two canids have ancestry indistinguishable from Eurasian wolves, with no shared ancestry with domestic dogs of the lineage. Their genome-wide heterozygosity is lower than that observed in 72 previously published ancient wolf genomes, and instead comparable to dogs. Stable isotope data (δ C and δ N) reveals a diet rich in marine protein, which is consistent with habitation alongside the human groups who used Stora Karlsö as a seal-hunting, fowling, and sea fishing station, and in the Bronze Age probably also for grazing. Skeletal size is at the lower end of wolf variability, and one individual shows advanced pathology consistent with reduced mobility. While other scenarios are possible, a parsimonious explanation is that these wolves were brought to the island by humans and were possibly under human control.